First laugh : welcome, baby! - Tahe, Rose Ann; Flood, Bo (Charlesbridge, 2018)
"A Navaho family welcomes a new baby into the family with love and ceremony, eagerly waiting for that first special laugh. Includes brief description of birth customs in different cultures." --